2016
DOI: 10.1159/000446776
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement between Skin Prick Tests and Specific IgE in Early Childhood

Abstract: Background: Accurate diagnosis of allergic sensitization is essential in clinical practice and allergy research, and the choice of assessment method may have an important impact. The PASTURE study (Protection against Allergy: Study of Rural Environment) examines the influence of exposure to a dairy farm environment on the occurrence of allergy in a cohort of rural European children from birth to 10 years. The aim of our study was to analyze agreement between skin prick tests (SPTs), to aeroallergens and food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
7
1
4
Order By: Relevance
“…The area under the curve (AUC) obtained with SPT was not significantly different from that obtained with sIgE in recent research made by Chauveau A. et al [10,11]. For asthma and hay fever, SPT (cutoff value at 3 mm) had a significantly higher specificity (P < 0.0001) than sIgE (cutoff value at 0.35 IU/mL) and the specificity was not different between both tests (P=.1088).…”
mentioning
confidence: 68%
“…The area under the curve (AUC) obtained with SPT was not significantly different from that obtained with sIgE in recent research made by Chauveau A. et al [10,11]. For asthma and hay fever, SPT (cutoff value at 3 mm) had a significantly higher specificity (P < 0.0001) than sIgE (cutoff value at 0.35 IU/mL) and the specificity was not different between both tests (P=.1088).…”
mentioning
confidence: 68%
“…Serum sIgE emerges as an alternative test in the field of allergy diagnosis. In some countries, for reasons of conformity, it is resorted to an estimate of the atopic state in young children solely by measuring the level of sIgE (circulating IgE) for certain allergens in the serum [2].…”
Section: Markers Of Allergic Status -Skin Prick Test Total and Specimentioning
confidence: 99%
“…While a few studies have shown some discordance between these two methods in adults, most studies were performed in the hospital setting, whereas far fewer studies have compared SPTs and sIgE head‐to‐head in childhood, and fewer still have done so in unselected birth cohorts . The results of a substudy on atopic sensitization in French children from the PASTURE (Protection against Allergy: STUdy in Rural Environment) cohort suggested disagreement between SPT and sIgE in the first 6 years of life …”
Section: Introductionmentioning
confidence: 99%
“…5 The results of a substudy on atopic sensitization in French children from the PASTURE (Protection against Allergy: STUdy in Rural Environment) cohort suggested disagreement between SPT and sIgE in the first 6 years of life. 6 The discordance between these two tests raises the question as to whether one test method is better associated with allergic diseases than the other. Allergic rhinitis is known to be well correlated with both tests, 7 but little is known about other allergic diseases, 8 especially in childhood.…”
mentioning
confidence: 99%